ELABORACIÓN DE UN PLAN DE MARKETING PARA LA EMPRESA FUENTE DE SODA “EL JUGO NATURAL DE LA CIUDAD DE LOJA - Cango García, Patricia Johanna (2015)
EL JUGO NATURAL is a company dedicated to providing the cafeteria, bakers in the city of Loja and its purpose is to provide a wide range of premium products to its customers, however this organization and with many years in the market has not raised an organizational addressing that supports the competitive environment in which it operates, therefore has proposed a marketing plan to help consolidate this organization as a strong and competitive entity. The development of this thesis project titled MARKETING PLAN FOR THE COMPANY "soda fountain natural juice" which aims to analyze the internal and external factors in the company, in order to identify opportunities, threats, strengths and weaknesses this company and define the most appropriate ways for business strategies. For today the company dedicated to the service of caferías and customer focus in planning marketing strategies thus be within the competitive market and better meet consumers through an efficient and effective service enable them to rationalize their resources more productive and competitive. In the external analysis it is referring to macro- and micro. In the Macroenvironment the PEST analysis where the factors having impact on the company, determined political factor was performed, changing laws and rules in labor leads to high costs for the company and secondly the law handmade rating benefits the company in a positive way by decreasing your expenses. 8 In a variable economic factor that has great impact on the company's growth pace of inflation of 3.53% to 4.05% generating a rise in the price of agricultural products thus causing a rise in prices the products offered natural juice. The presence of computer solutions for businesses and high Internet use which are an opportunity for the company will market coverage stands at the technological factor. In the analysis of micro-analysis of the five forces of Michael Porter's competition it was held, to which could reach the conclusion that the sector of the company is in constant growth allowing the entry of new competitors, also among competition is very intense because there are 40 cafes and fountains of soda causing bargaining power with customers in their favor altering the prices of products. Once the necessary information from the external analysis Matrix EFE evaluation External factors, where opportunities and threats of the company is identified is performed. The internal analysis of the company's functional areas of the company are considered and to obtain the information was necessary to interview the company manager Lic. Jeanne Monteros Mercedes Jaramillo, and implement surveys to 15 employees. In the organizational component, it was found that the company does not have a mission, vision, objectives, organization and functions manuals, there is no planning activities and you can see the lack of organization. 9 In the organizational component, it was found that the company does not have a mission, vision, objectives, organization and functions manuals, there is no planning activities and you can see the lack of organization. In the commercial area we refer to the products offered by the company are natural products café in which it is mentioned that the attention and customer service is not satisfactory in 23.83%, and the delay in delivering the products have a level of dissatisfaction of a 39.89% The customers rely on the quality and price of the products they buy, you can also show that consumers are informed about the company through advertising business card via phone call and 10.88% through internet. In the labor component; Domestically among the most relevant results that are reflected in employee surveys, in terms of training one 63,64% it has not received any kind of training, as well as the 59.09% consider that their activities are carried out in a good working environment, however 100% of the staff recognize that their obligations are not properly defined in the manual governing functions within the company. The component processes; identifies "natural juice" has problems delivering orders on time, failure finished products thus causing increased costs to the company. Once the internal analysis conducted in each area of the company, the parent Internal Factors Evaluation (EFI) where you can identify the strengths and opportunities that have Paco Advertisement is performed. 10 Strengths, Weaknesses and Threats: SWOT matrix in the internal and external factors affecting the company and are being analyzed. And then ask the strategies to reduce threats and overcome weaknesses. And finally to research the approach of the strategic objectives is done. The proposal has the following objectives: • The first objective is to improve the systems of organization and management of natural juice company by raising an organizational philosophy and an organizational management structure at a cost of $ 452.50 • The second objective is to promote personal and professional development of employees, motivation and loyalty to the company organizational purposes natural juice which has a cost of $ .1.318,00 • The third objective is to increase sales of products of the company "natural juice" and improve corporate image, through a strategic plan advertising and promotions at a cost of $ 1.050.00.